2008
DOI: 10.3892/or.20.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors and aspirin interact synergistically to induce cell death in ovarian cancer cells

Abstract: Abstract. Histone deacetylase inhibitors (HDIs) as well as non-steroidal anti-inflammatory drugs including aspirin show promise as antineoplastic agents. The treatment with both HDIs and aspirin can result in hyperacetylation of proteins. In this study, we investigated whether HDIs and aspirin interacted in inducing anticancer activity and histone acetylation. We found that the HDIs, suberoylanilide hydroxamic acid and sodium butyrate, and aspirin cooperated to induce cell death in the ovarian cancer cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…4). In addition, Sonnemann et al (60) have shown that HDIs and aspirin synergistically induce cell death in OC cells in vitro independent of cyclooxygenase. Because aspirin and other nonsteroidal anti-inflammatory drugs, in addition to inhibiting cyclooxygenase activity, inhibit IKK activity (41,61), it is possible that the observed HDI/aspirin synergistic effect was mediated by IKK inhibition and suppression of the IL-8 expression induced by HDAC inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…4). In addition, Sonnemann et al (60) have shown that HDIs and aspirin synergistically induce cell death in OC cells in vitro independent of cyclooxygenase. Because aspirin and other nonsteroidal anti-inflammatory drugs, in addition to inhibiting cyclooxygenase activity, inhibit IKK activity (41,61), it is possible that the observed HDI/aspirin synergistic effect was mediated by IKK inhibition and suppression of the IL-8 expression induced by HDAC inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…18 TSA causes apoptosis through the inhibition of cell viability, as well as proliferation of cells expressing apoptosis-related proteins and activation of those proteins in a variety of cancer cells, including human breast, gastric, ovarian, small-cell lung, and cervical cancer cells. [19][20][21][22][23] TSA is not only a potential inducer of apoptosis but also involved in reprogramming efficiencies of stem cells. 24 Although several studies have reported that TSA has a potential inhibitory effect on cancer, there is limited information on the combination effect of TSA particularly with nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…At the histone level, it has also been reported to induce and inhibit of deacetylases with direct acetylation of histones [131][132][133]. Studies has also reported Aspirin inhibiting AR related transcriptional activity in both androgen dependent and independent prostate cancer [134] while regulating the aberrant overexpression of AKR1C3 gene in certain breast cancer cell lines [135].…”
Section: Aspirinmentioning
confidence: 99%